Influence of Customer Relationship Management and Service Quality on Customer Loyalty Mediated by Customer Satisfaction - A'am Ar Rosyad; Ika Febrilia; Rahmi (Sean Institute, 2023)
This study aims to determine the effect of customer relationship management and service quality on loyalty mediated by customer satisfaction with case studies on e-commerce Shopee users in Jabodetabek. The variables measured in this study are customer relationship management (CRM), service quality, customer loyalty, and customer satisfaction. The population in this study is Jabodetabek people who use e-commerce Shopee. This study uses a quantitative type using a probability sampling technique. The selected sample in the Jabodetabek study is people who actively use e-commerce Shopee by making at least 5 purchases in the last 3 months with an age range of 17-39 years old. This study uses SEM data analysis model on AMOS version 21. The results of this study indicate that there is an influence between CRM and customer loyalty. CRM influences customer satisfaction. And service quality influences customer loyalty. Service quality affects customer satisfaction. Likewise, service quality can mediate customer loyalty and customer satisfaction. CRM can mediate customer loyalty and customer satisfaction. Likewise, service quality can mediate customer loyalty and customer satisfaction. CRM can mediate customer loyalty and customer satisfaction. Likewise, service quality can mediate customer loyalty and customer satisfaction. CRM can mediate customer loyalty and customer satisfaction.